2016
DOI: 10.1371/journal.pone.0154284
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Norovirus GII.17 Variants among Children with Acute Gastroenteritis in South Korea

Abstract: Of 1,050 fecal specimens collected from January 2013 to August 2015 from children with acute gastroenteritis, 149 (14.2%) were found to be positive for norovirus. Norovirus GII was the most predominant genogroup (98.65%; 147 of 149). The genotypes detected in this study were GI (2; 1.3%), GII.Pe-GII.4 (109; 73.1%), GII.P17-GII.17 (16; 10.7%), GII.P12-GII.3 (8; 5.4%), GII.P12-GII.12 (8; 5.4%), GII.P4-GII.4 (5; 3.4%), and the recombinant GII.Pe-GII.17 (1; 0.7%). Of these, the novel GII.17 strain was the second m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 33 publications
4
23
0
Order By: Relevance
“…RdRp/capsid genotypes were determined and that 12 of them were distinct in RdRp genotypes and capsid genotypes. All of the discordant RdRp/capsid genotypes were suspected to be recombinant strains, and most of them have been reported elsewhere [14,16,17,23,37,41]. Although more analysis of the junction of ORF1 and ORF2 is needed to confirm the recombination site in our study, the results clearly suggest that this phenomenon is very common in NoVs, as observed elsewhere.…”
Section: The Analysis Of Combined Nov Gii Genotypes Conducted In Thissupporting
confidence: 78%
“…RdRp/capsid genotypes were determined and that 12 of them were distinct in RdRp genotypes and capsid genotypes. All of the discordant RdRp/capsid genotypes were suspected to be recombinant strains, and most of them have been reported elsewhere [14,16,17,23,37,41]. Although more analysis of the junction of ORF1 and ORF2 is needed to confirm the recombination site in our study, the results clearly suggest that this phenomenon is very common in NoVs, as observed elsewhere.…”
Section: The Analysis Of Combined Nov Gii Genotypes Conducted In Thissupporting
confidence: 78%
“…Furthermore, PCR and sequencing of the long fragment covering the ORF1–ORF2 junction were successful in 2 samples, both genotyping as GII.P17-GII.17. Sequences had high homology (99.91%) to several Asian strains, such as Hu/GII.P17_GII.17/KR/2014/CAU-265 ( 6 ). …”
mentioning
confidence: 99%
“…In the past decades, NoV GII.4 was identified as the most predominant genotype involved in numerous epidemic outbreaks, for example, in 2002,2004,2006,2009 and 2012 [37]. Recently, a novel NoV GII.17 variant has emerged and is responsible for multiple disease outbreaks mainly in China and Japan [9,[11][12][13][14][15][16][17][18][19][20][21][22]. GII.17 appeared as a dominant strain replacing the GII.4 strain in these regions during 2014-2015 [23].…”
Section: Discussionmentioning
confidence: 99%
“…In the winter of 2014-2015, a rare NoVs genotype, GII.17, emerged in most of the East Asian regions including China (Guangdong [9][10][11][12][13], Jiangsu [14], Zhejiang [15], Hebei [16], Hong Kong [17], Taiwan [18], Beijing [19], and Shanghai [20], Japan [21] and South Korea [22]). Soon after, the novel GII.17 strain became the most predominant NoV strain, replacing the pandemic strain GII.4 Sydney 2012, responsible for the majority of gastroenteritis outbreaks in this region [23].…”
Section: Introductionmentioning
confidence: 99%